2014
DOI: 10.1038/eye.2014.40
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoexfoliation syndrome and coronary artery ectasia

Abstract: In this study, we found a possible association of pseudoexfoliation and coronary artery ectasia. Coronary artery ectasia patients had higher prevalence of pseudoexfoliation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Reduced tissue expression levels of LOXL1 have been related to pronounced structural elastotic and biomechanical alterations of elastin-rich connective tissues, such as the lamina cribrosa and blood vessel walls, thereby increasing the risk for pressure-induced optic nerve damage and cardiovascular complications2433. Accordingly, our group and others have described a significant association between PEX and systemic disorders of elastic tissues, that is, aortic aneurysms, coronary artery ectasia, renal artery stenosis and pelvic organ prolapse67839404142. Changes in LOXL1 gene expression have been observed in many other conditions, including aging4344 and disorders involving weakening of elastic connective tissues454647.…”
Section: Discussionmentioning
confidence: 95%
“…Reduced tissue expression levels of LOXL1 have been related to pronounced structural elastotic and biomechanical alterations of elastin-rich connective tissues, such as the lamina cribrosa and blood vessel walls, thereby increasing the risk for pressure-induced optic nerve damage and cardiovascular complications2433. Accordingly, our group and others have described a significant association between PEX and systemic disorders of elastic tissues, that is, aortic aneurysms, coronary artery ectasia, renal artery stenosis and pelvic organ prolapse67839404142. Changes in LOXL1 gene expression have been observed in many other conditions, including aging4344 and disorders involving weakening of elastic connective tissues454647.…”
Section: Discussionmentioning
confidence: 95%
“…In the same cohort, no association of PEX with the 30-year all-cause mortality was found [70 && ]. Conversely, several case-control studies have reported association of PEX with specific systemic diseases, such as renal artery stenosis and abdominal aorta aneurysm with the use of Doppler ultrasonography [71] (in the same cohort no association with impaired renal function was reported) [72], or coronary artery ectasia by the means of coronary angiography [73], or with lower peak systolic velocities by myocardial tissue Doppler imaging or with increased carotid intima-media thickness by carotid ultrasound measurements [74]. A recent meta-analysis tried to combine the existing data on the association of PEX with vascular diseases and included 16 eligible studies (8533 PEX cases and 135 720 controls) [75].…”
Section: Association Of Pseudoexfoliation With Systemic Diseasesmentioning
confidence: 87%
“…Particular vascular diseases that have an apparent association with the PEX include those that affect the arterial wall. According to Akdemir et al, the PEX was more common in patients with coronary artery ectasia [33]. A study conducted in Australia detected a possible link between the PEX and vascular events, including AMI and stroke [32].…”
Section: Discussionmentioning
confidence: 99%